(3JdNjU cJGH JNLjd ef MQa GdEfLjds - (3CHh GdaVd GdeGdcj GdSYhOis; (3GdLYaQj , UGdM Hf GdMSjf GdLYaQj, CHhGdHbGA,J (B668 (3g` s
(3ChdgG (B:s
(3hHYO abO JOHQJ eG Cdag GdTjN GdEeGeCHh GdHbGA UGdM Hf GdMSjf GdLYaQi cJGH JfLjd ef MQa GdGfLjd hCbJHSJ ef CfhGQg eG GgJOjJ Hg s
(3BNQgG (B:s
(3hCf jMQS bdhHfG hCagGefG ef ehGQO GdWZjGf hecGFO GdTjWGf hdG Mhd hdG bhI EdG HGddg GdYdi GdYXje s
(3HChdg agQSJ ddcJGHs
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
Keywords: (3GdJhMjO hGdedd hGdfMds